Community-Based Resources for Concussion Management - Crawford, Nannette; Sirmon-Taylor, Bess (Seminars in Speech and Language, 2014)
Speech-language pathologists can serve an important role as members of interdisciplinary treatment teams in the rehabilitation of concussion-related cognitive-communicative changes in the community setting. This article discusses the continuum of care for individuals who have experienced concussion and the importance of appropriate assessment and functionally based intervention. Factors such as executive function impairments, sensory overload, and cognitive exertion can yield subtle deficits that can impact functional return to work or school. Community resources such as support groups are discussed, as well as the impact of state and federal policies related to concussion on community activities.
Keywords: Concussion management; community resources; rehabilitation